Improving canteen's service and operations management: A case study using modelling and simulation approach - Lee, Khai Loon; Puteri Nurhazira, Romzi (Penerbit UTHM, 2021)
Operating a canteen business in an audio and visual innovation centre is a small business. However, it required good operating practices to be efficient and successful. Having good operating procedures required everyone to know its goals, objectives and be familiar with its policies.